Determinants of Oral Health Behavior among Preschool Children: Application of the Theory of Planned Behavior - Raheleh Soltani; Gholamreza Sharifirad; Behzad Mahaki; Ahmad Ali Eslami (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Dental caries is the most common chronic disease among children. Determinants of children's oral health behavior should be better understood and known. Purpose: This study aimed to investigate the predictive factors of oral health behavior among preschool children based on the theory of planned behavior (TPB). Materials and Method: This cross-sectional study included 833 mother-child pairs referring to twenty health centers in Tabriz, North-West Iran, from August 2014 to November 2015. The participants were selected by multi-stage stratified random sampling. Data were collected through self-administered questionnaires completed by the participating mothers. The questionnaire consisted of demographic characteristics, oral health behavior, and TPB structures (attitude, subjective norms, perceived behavioral control, and intention). Results: The mean±standard deviation (SD) of children's age was 4.6±1.1 years (ranging 3-6), and 52% were boys. 20.3% of mothers had university degrees. The mean (SD) score of children's oral health behavior was 5.8 (±1.9) out of 8. Muliple regression analysis revealed a positive relationship between all TPB structures and children's oral health behavior F(11,821)=41.8, R=0.6, (p< 0.001). Furthermore, the TPB structures explained 35% and 29% of the variance in children's oral health behavior and maternal intention towards it, respectively. Conclusion: Based on the current finding, TBP is the important predictor of children's oral health behavior. Effective promotion interventions could be designed based on this predictor to help improving the children's oral hygiene behavior.